Preparation of inclusion complex between ellagic acid and hydroxypropyl-β-cyclodextrin - Thi Lan, Pham; Van Cuong, Bui; My Hanh, Le Thi; Phuong Lan, Nguyen Thi; Roman, Kushnir; Tatyana, Usacheva (Vietnam Journal of Biotechnology, 2023)
In recent years, the research and discovery of antioxidants of natural origin, such as those found plants, have increased dramatically. Ellagic acid is a bioactive compound found in many fruits and vegetables, which carries many biological activities, such as antioxidant, anti-inflammatory, anti-cancer and antibacterial activities. However, the low solubility of ellagic acid in water decreases its practical application. In this study, a complex of ellagic acid with hydroxypropyl-cyclodextrin was synthesized in the water-ethanol solvent. The results showed that the solvent with a volume content of EtOH of 20% was the most suitable for complex formation, with complexation yield of 46%. The complex was characterized by FTIR, DSC methods. The infrared spectrum of the complex is similar to that of HP-β-CD, however, the intensity and position of some oscillations in the complex have changed significantly, compared to spectra of EA and HP-β-CD. The sharp adsorbance band at 3475 cm-1 of the O-H bond of EA was not observed in the spectrum of the complex, indicating that the O-H group participated in the bonding and covered by the hollow cavity of the HP-β-CD molecules. The DSC curve of the complex shows that the melting points of EA and HPβCD in the complex are declined in terms of temperature and intensity. This is evidence that there is a complex interaction between EA and HPβCD. The complexation improved the solubility and antioxidant activity of EA. Especifically, the solubility of EA was increased by 3.2 times compared to raw EA; EC50 value of EA was reduced from 5.3x10-5 to 4.9x10-5mol. L-1 after complexation.